Analisis Normatif Penegakan Hukum Tindak Pidana Pencurian - Iman Hidayat (Universitas Batanghari Jambi, 2023)
The most essential legal basis in Indonesia is Pancasila and the 1945 constitution, in addition to other legal products. Basically there are many things that can be the cause of crime, especially from the point of view of the conditions or circumstances of society, for example poverty or economic downturn is the cause of a lot of theft, lots of juvenile delinquency, rampant corruption that causes tendencies to rebel or reluctance of people to obey the rules, regulations in force, the absence of legal certainty that can grow the seeds of hatred, especially between the weak against the strong. Likewise, the legal awareness of the general public or the local community in many ways can be seen as a symptom of a crime or crime. Theft that occurs at this time can be caused by the difficulty of finding work, due to the number of people who do not match employment opportunities, many people who drop out of school, because a school graduation certificate is a formal requirement in finding a job. Therefore, people use shortcuts, namely working a little and can make a lot of money, even by committing the crime of theft that violates the law. Punishments or crimes that can ensnare those who are proven to have committed the crime of theft, namely imprisonment for a maximum of 5 (five) years for ordinary theft or imprisonment for a maximum of 9 (nine) years, if the theft was preceded, accompanied or followed by violence and even the death penalty or imprisonment for life if the crime of theft is committed by two or more persons which results in serious injury or death of a person. The crime of theft is regulated in Chapter XXII Book II of the Criminal Code (KUHP), there are 5 articles that regulate the crime of theft consisting of Articles 362, 363, 364, 365 and 367.